Role of an adaptor protein Lin‐7B in brain development: possible involvement in autism spectrum disorders. (26th September 2014) - Mizuno, Makoto; Matsumoto, Ayumi; Hamada, Nanako; Ito, Hidenori; Miyauchi, Akihiko; Jimbo, Eriko F.; Momoi, Mariko Y.; Tabata, Hidenori; Yamagata, Takanori; Nagata, Koh‐ichi
Abstract Using comparative genomic hybridization analysis for an autism spectrum disorder (ASD) patient, a 73‐Kb duplication at 19q13.33 (nt. 49 562 755–49 635 956) including LIN7B and 5 other genes was detected. We then identified a novel frameshift mutation in LIN7B in another ASD patient. Since LIN7B encodes a scaffold protein essential for neuronal function, we analyzed the role of Lin‐7B in the development of cerebral cortex. Acute knockdown of Lin‐7B with in utero electroporation caused a delay in neuronal migration during corticogenesis. When Lin‐7B was knocked down in cortical neurons in one hemisphere, their axons failed to extend efficiently into the contralateral hemisphere after leaving the corpus callosum. Meanwhile, enhanced expression of Lin‐7B had no effects on both cortical neuron migration and axon growth. Notably, silencing of Lin‐7B did not affect the proliferation of neuronal progenitors and stem cells. Taken together, Lin‐7B was found to play a pivotal role in corticogenesis through the regulation of excitatory neuron migration and interhemispheric axon growth, while further analyses are required to directly link functional defects of Lin‐7B to ASD pathophysiology.<boxed-text content-type="graphic" id="jnc12943-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Lin‐7 plays a pivotal role as a scaffold protein in synaptic development and plasticity. Based on genetic analyses we identified mutations in LIN‐7B gene in some ASD (autism‐spectrum disorder) patients. Functional defects in Lin‐7B caused abnormal neuronal migration and interhemispheric axon growth during mouse brain development. Thus, functional deficiency in Lin‐7B could be implicated in clinical phenotypes in some ASD patients through bringing about abnormal cortical architecture.